Influence of abutment-to-fixture design on reliability and failure mode of all-ceramic crown systems - Delben, Juliana A. [UNESP]; Barao, Valentim A. R.; Ferreira, Mayara B. [UNESP]; Silva, Nelson R. F. A. da; Thompson, Van P.; Assunção, Wirley Goncalves [UNESP] (Elsevier B.V., 2014)
Objective. Evaluate the effect of implant connection designs on reliability and failure modes of screw-retained all-ceramic crowns.Methods. Central incisor ceramic crowns in zirconia abutments were screwed and torqued down to external hexagon (EH), internal hexagon (IH) and Morse taper (MT) implant systems. Single-load-to-fracture (SLF) test (n = 4 per group) determined three step-stress fatigue profiles with specimens assigned in the ratio of 3:2:1. Fatigue test was performed under water at 10 Hz. Use level probability Weibull curves and reliability for missions of 50,000 cycles at 400 N and 200 N were calculated (90% confidence bounds-CB). Weibull probability distribution (90% CB) was plotted (Weibull modulus vs characteristic strength) for comparison between the groups. Fractographic analyses were conducted under polarized-light microscopy and SEM.Results. Use level Weibull probability calculation indicated that failure was not associated with fatigue in groups EH (beta = 0.63), IH (beta = 0.97) and MT (beta = 0.19). Reliability data for a mission of 50,000 cycles at 400 N revealed significant reliability differences between groups EH (97%), IH (46%) and MT (0.5%) but no significant difference at 200 N between EH (100%) and IH (98%), and IH and MT (89%). Weibull strength distribution (figure) revealed beta = 13.1/eta = 561.8 for EH, beta = 5.8/eta = 513.4 for IH and beta = 5.3/eta = 333.2 for MT. Groups EH and IH exhibited veneer cohesive and adhesive failures. Group IH also presented adhesive failure at zirconia/titanium abutment insert while MT showed fracture at abutment neck.Significance. Although group EH presented higher reliability and characteristic strength followed by IH and MT, all groups withstood reported mean anterior loads. (C) 2014 Academy of Dental Materials. Published by Elsevier Ltd. All rights reserved.
Keywords: Reliability; Dental implants; Zirconia; Implant-supported prosthesis